(untitled) (Faridpur Medical College Journal, 2018)
Schizencephaly is an extremely rare developmental birth defect characterized by abnormal slits or clefts in the cerebral hemispheres extending from the lateral ventricle to the cerebral cortex. The margins of the cleft are lined with heterotropic, dysplastic gray matter. The causes of schizencephaly are heterogenous and include teratogens, prenatal infarction/infections, maternal trauma, or EMX2 mutations. It is a central nervous system disorder with variable presentations. People with this disorder commonly have developmental delays, delays in speech and language skills, seizures disorder and problems with brain-spinal cord communication. This condition is present at birth and manifests early in life. This patient presented with seizure and growth retardation and investigation revealed bilateral Schizencephaly with Septo optic dysplasia. Faridpur Med. Coll. J. Jan 2018;13(1): 50-52